Optimization of Computed Tomography Imaging with Maximum Intensity Projection (Mip) Reconstruction in Detecting Solid Pulmonary Nodules Smaller than 5 Mm at the National Lung Hospital - Luong, Hoang Van; Thuong, Nguyen Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2025)
Objective: To evaluate the role of computed tomography (CT) with maximum-intensity-projection (MIP) reconstruction at different slab thicknesses in detecting solid pulmonary nodules smaller than 5 mm. Materials and methods: Chest CT data from 39 patients with solid pulmonary nodules less than 5 mm in diameter were retrospectively analyzed. Each dataset was reconstructed into four image series: standard CT images (MIP0) and MIP images with slab thicknesses of 5, 10, and 15 mm. Two experienced radiologists independently reviewed all image series with at least a two-week interval between readings to minimize recall bias. The number, size, margin, and location of detected nodules were recorded. Interobserver agreement and differences in detection performance among MIP levels were statistically analyzed. Results: Most nodules had smooth margins and were located peripherally. Interobserver agreement for nodule detection was excellent across all MIP levels (p > 0.05; R² = 0.866). The detection rate of solid nodules smaller than 5 mm was highest on 10-mm MIP images compared with other reconstruction series. Conclusion: Computed tomography with 10-mm maximum-intensity-projection reconstruction is extremely effective for detecting solid pulmonary nodules smaller than 5 mm. Keywords: pulmonary nodule, maximum-intensity-projection.